Penetrating Pellet Gun Injury to the Neck and Embolization to the Right Ventricle - Victoria Fanucci, BS; Utkarsh Kohli, MD; Federico Seifarth, MD; Casey McCluskey, MD; Alyssa Fazi, MD; Dhaval Chauhan, MD (JACC: Case Reports)
Background: Air pellet rifles are marketed and available in the United States as toys despite their ability to cause significant injury. Over 360,000 children were seen in the emergency department for penetrating injuries involving nonpowder firearms between 1990 and 2016. Case Summary: We report a 10-year-old boy with a penetrating injury to the neck, resulting in embolization of the pellet to the right ventricle through the right internal jugular vein. The patient was successfully treated with removal of the pellet by sternotomy. Discussion: Missile embolization through the venous system is usually seen in gunshot wounds below the diaphragm, contrary to what was observed in the patient presented. Given their unpredictable nature, there are no standardized guidelines for managing missile emboli, although retrieval is recommended in most cases. Take-Home Message: There is a need to establish standardized treatment guidelines for missile emboli and educate parents on the dangers of penetrating injuries involving nonpowder firearms.